1H MR Spectroscopy in Gliomatosis: Is there a Sensitivity Issue?. (11th September 2011) - Szewczyk-Bieda, M.; Kanodia, A. K.; Main, G.; Eljamel, M. S.
Abstract : Objective . 1 H MR spectroscopy (MRS) is widely performed for assessment of brain tumours and is considered a highly sensitive technique capable of differentiating benign from malignant conditions and tumour grading. Method . We present a case of a 69 year old woman who was suspected to have gliomatosis on MRI. Results . MRS performed using single voxel and chemical shift/multivoxel techniques was within normal limits. A repeat scan 6 months later showed progressive disease, and biopsy was performed that proved the diagnosis of glioblastoma. Conclusion . Normal MRS in a patient with suspicion of gliomatosis on MRI should not reassure clinicians into assuming a benign aetiology or a good prognosis in short term.